Improvement of Cane Yield and Sugar Yield of Sugarcane (Sacharrum officinarum) Through Maintaining Ratoon - FITRININGDYAH TRI KADARWATI; BUDI SANTOSO; AHMAD DHIAUL KHULUQ (Jurnal Penelitian Tanaman Industri, 2015)
ABSTRACTThe level of sugarcane yield in dry land or rainfed generally still low at 40 to 50 tons per hectare. Farmers prefer maintenance of sugarcane than unloading ratoon cane (RC). This can be understood because unloading RC requires high cost, especially in the purchase of seed cane and tillage. Approach through maintaining ratoon techniques are expected to increase production and sugar yield. The research purposes to obtain cane yield and sugar yield RC optimally with maintaining ratoon techniques in dry land. Research has conducted in the Ngimbang, Lamongan district from June 2013 until August 2014. Sugarcane varieties used PS 862 (early ripening) belong to farmers. The study compiled by randomized block design (RBD) and repeated 3 times. The treatment consisted of 1). Replanting; 2). Off barring; 3). Organic fertilizer; 4). Maintaining 10 plants/m; 5). Giving PGR; 6). The package of (1+2); 7). The package of (1+2+3); 8). The package of (1+2+3+4); 9). The package of (1+2+3+4+5); and 10). Control. The results showed that the complete treatment of maintaining ratoon (replanting, off barring, organic fertilizer, maintaining 10 plants/m and PGR) obtained the highest value on the highgrowth parameters include 304.67 cm and a diameter of 3.16 cm, while the production parameters include the stalk number 5.73 stalk/m, stalk weight 1.29 kg/stalk, and stalk length 264.11 cm. Maintaining ratoon could gave the best cane yield and sugar yield than ratoon plants without maintaining ratoon cane with an increase of cane yield 16.20 tons/ha (32.14%) and an increase of sugar yield 1.38% (25.60%). Maintaining on ratoon cane 4th on rainfed significantly increase the production of sugarcane per hectare although not linear with increasing sugar yield.Keywords: Maintaining ratoon, PS 862 varieties, dry land, Sacharrum officinarum PENINGKATAN PRODUKSI DAN RENDEMEN TEBU (Sacharrum officinarum) MELALUI RAWAT RATOONABSTRAKTingkat produktivitas tebu di lahan kering atau tadah hujan umumnya masih rendah sebesar 40 sampai dengan 50 ton per hektar. Para petani tebu lebih memilih rawat ratoon daripada membongkar tebu ratoon (RC). Hal tersebut dapat dipahami karena membongkar ratoon membutuhkan biaya yang lebih besar, terutama dalam pembelian bibit tebu dan olah tanah. Pendekatan melalui teknik rawat ratoon diharapkan dapat meningkatkan produksi dan rendemen tebu. Tujuan dari penelitian untuk memperoleh pertanaman tebu dengan teknik rawat ratoon yang berproduksi dan berendemen optimal di lahan kering. Penelitian dilaksanakan di Ngimbang, Kabupaten Lamongan mulai Juni 2013 sampai Agustus 2014. Varietas tebu yang digunakan yaitu PS 862 (masak awal) milik petani. Penelitian disusun dengan Rancangan Acak Kelompok (RAK) yang diulang 3 kali. Perlakuan terdiri atas 1). Sulam; 2). Pedot Oyot; 3). Pupuk Organik; 4). Pertahankan 10 tanaman/m; 5). Pemberian ZPT; 6). Paket (1+2); 7). Paket (1+2+3); 8). Paket (1+2+3+4); 9). Paket (1+2+3+4+5); dan 10). Kontrol. Hasil penelitian menunjukkan bahwa perlakuan lengkap pada rawat ratoon (sulam, pedot oyot, pupuk organik, 10 tanaman/m dan ZPT) diperoleh nilai tertinggi pada parameter pertumbuhan meliputi tinggi 304,67 cm dan diameter 3,16 cm, sedangkan parameter produksi meliputi jumlah batang terpanen 5,73 batang/m, bobot batang 1,29 kg/batang, dan panjang batang 264,11 cm. Rawat ratoon dapat memberikan hasil produksi dan rendemen terbaik dibandingkan tanaman tebu tanpa rawat ratoon dengan kenaikan sebesar 16,20 ton/ha (32,14%) dan peningkatan angka rendemen 1,38% (25,60%). Rawat ratoon RC 4 pada lahan tadah hujan secara signifikan meningkatkan produksi tebu perhektar meskipun tidak linier dengan peningkatan rendemen gula.Kata kunci: Rawat ratoon, varietas PS 862, lahan kering, Sacharrum officinarum